Adérito Sedas Nunes and the bishop of Porto in 1958 - Barreto, José (2007)
The author tells of how the paths of sociologist Adérito Sedas Nunes, who later founded the Instituto de Ciências Sociais and the journal Análise Social, and of the «sociological» bishop D. António Ferreira Gomes crossed in 1958. In 1959 Salazar exiled the bishop abroad for a long period. At a pivotal moment of political division among catholics, both men wished to see the Church disengage from corporativism and the Estado Novo, already with an eye to the post-Salazarist future.